Rancang Bangun Computer Network e-dictionary Application Berbasis Android - Rizki, Yovan; Widyastuti, Rini; Amelia, Rizka (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to produce an Android-based computer network E-Dictionary application. This e-dictionary application is to assist users in searching for terms in computer networks. The method used in this study is the waterfall method, while in programming and user interface design using the Sketchware application tool. In designing this dictionary application system, using UML (Unified Modeling Language) as a system visualization into the software. The results of this study are computer network e-dictionary applications that can be used on Android-based smartphones if connected to the internet. This e-dictionary can run on an Android-based smartphone with version 5.0 and above and can also be run on a personal computer (PC) using an emulator.